Keratinocyte-derived VEGF-A is an essential pro-migratory autocrine mediator, acting through the KDR/GEF-H1/RhoA pathway - Maksimoska, Vida; Dan, Qinghong; Rambharack, Neetu; Szászi, Katalin (Frontiers in Cell and Developmental Biology, 2025)
IntroductionKeratinocytes proliferate, migrate and differentiate to achieve skin re-epithelialization following injury. They also secrete soluble mediators to induce inflammation and orchestrate restoration of the skin barrier. However, dysregulated mediator release can cause sustained inflammation, leading to pathological healing. The small GTPase RhoA is key for cell migration, but the molecular mechanisms controlling Rho proteins in keratinocytes remain incompletely characterized. The overall objective of the current study was to explore the connection between inflammation-induced keratinocyte mediator release and enhanced migration, and to identify specific RhoA regulators involved.MethodsThe study was done using HaCat cells and primary adult keratinocytes. A multiplex cytokine panel was used to simultaneously detect 48 mediators secreted from TNFα-stimulated HaCat cells. Cell migration was followed using live timelapse imaging. Target proteins were silenced using siRNA or inhibited with drugs. RhoA and GEF-H1 activation were detected using affinity precipitation assays with GST-RBD or GST-RhoA (G17A). Key proteins were visualized using immunohistochemistry in an MC903-induced mouse model of atopic dermatitis.ResultsWe showed that keratinocytes secreted an array of soluble factors, including VEGF-165. Secretion of VEGF-165 was augmented by TNFα through SP1, HIF1α and NFκB. TNFα or VEGF-165 potently augmented HaCaT collective migration. Depletion of VEGF-A or VEGF Receptor2 (referred to as Kinase Insert Domain Receptor, KDR) or inhibition of RhoA reduced basal migration and prevented the pro-migratory effect of TNFα. Both VEGF-165 and TNFα increased KDR phosphorylation. VEGF-165 activated GEF-H1 (ArhGEF2) through KDR and ERK1/2. VEGF-165 also promoted GEF-H1 phosphorylation on S886. GEF-H1 depletion reduced VEGF-induced RhoA activation, slowed migration, and inhibited TNFα-induced VEGF-165 release. Finally, the epidermis in a mouse atopic dermatitis model had increased active RhoA, phospho-GEF-H1 and phospho-KRD levels.DiscussionWe showed that VEGF-A is a crucial paracrine factor, essential for basal and TNFα-induced keratinocyte migration. VEGF-165 activated RhoA through KDR and GEF-H1, and this pathway was upregulated in skin inflammation. Thus, GEF-H1 is critical for keratinocyte migration and VEGF-A secretion. Targeting the KDR/GEF-H1/RhoA pathway may reduce keratinocyte inflammatory responses, providing benefits in inflammatory skin disease.